(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
As we know, in modern teaching of foreign languages new methods and approaches are becoming compulsory to make the process of studying faster and effective. In this article has been discussed the merits of three language methods and the role of these approaches in a foreign language while studying it.